PECULIARITIES OF INFLUENCE OF MICROALLOYING WITH BORON ON STRAIN AGEING OF ROLLED WIRE OF STEEL SV-08G2C - A. M. Nesterenko; A. B. Sychkov; M. A. Zhigarev; S. Ju, Zhukova (Литьë и металлургия, 2010)
Influence of micro-alloying with boron on strain ageing of rolled wire of steel SV-08G2S is shown. A number of experiments on analysis of strain ageing of this steel are carried out